Biodiversity and ethnobotanical significance of vascular plants in the ecological trail and reservation site of indigenous trees (ECOTRIS), Ifugao Province, Philippines - Bimmoy, E D (Plant Science Today, 2025)
This study examines the macrofloral diversity and ethnobotanical significance of the Ecological Trail and Reservation Site of Indigenous Trees (ECOTRIS) in Ifugao Province, Philippines. The site is compartmentalized into four distinct land-use areas: an arboretum of native trees, a bamboo plantation, a fern grove, and a grassland with patches of trees. Biodiversity assessments were conducted across three plots established near the water tributaries, revealing the highest diversity index in the midstream plot, attributed to its dense canopy structure. Biodiversity indices using the Shannon index showed that the sampling plot near the stream had the highest value (3.02). In contrast, sampling sites near the marginal land and bamboo plantation had values of 2.56 and 2.78, respectively. Similarity indices indicated that Plot 1 had the highest similarity attributed to the high presence of pioneering species dominating the canopy, while Plot 3 exhibited lower species. Species Importance Value (SIV) analysis highlighted the pioneering species, particularly Melanolepis multiglandulosa Merr. dominated the sampling area. The study documented 22 edible plant species and 35 ethnobotanically significant trees, underscoring local floras’ cultural and medicinal value. This research emphasizes the ecological and cultural importance of preserving indigenous species and highlights the need for sustainable management practices to mitigate human-induced disturbances in the region. The findings underscore the potential of ECOTRIS as a field gene bank, advocating for sustainable management and the integration of indigenous conservation practices to enhance its ecological value and heritage.